Motion of No-Confidence By Members of The National Parliament in The 7th Constitutional Government of Timor Leste - Santos, Henrique dos; Luis , Reinaldo Francisco (Jurnal Locus Penelitian dan Pengabdian, 2025)
A motion of no confidence by members of parliament against the government is their right to follow up on government programs proposed in the state budget. However, what occurred during the seventh (VII) administration was a deliberate act by members of parliament, although constitutionally recognized. It still created a political anomaly, forcing the president of the Democratic Republic of Timor-Leste to decide to hold a new parliamentary election. This was intended to resolve the issues that arose and also had various implications for state administration and general governance. The president's decision constitutes an extralegal decision (the highest decision) that must be implemented as soon as possible to avoid a vacuum in the previously dissolved government. Therefore, a new general election is the right constitutional step to avoid further problems and allow for a return to normaly.